Microsoft SharePoint 2013 pocket guide - Curry, Ben (Benjamin Daniel) (Sams, 2013)
This is your most concise, practical reference to deploying, configuring, and running SharePoint 2013. Perfect for admins at all levels, it covers both technical topics and business solutions. SharePoint MVP Ben Curry focuses on the crucial step-by-step information for performing day-to-day tasks quickly, reliably, and well. No obscure settings, abstract theory, or hype… just help you can really trust—and really use! Install SharePoint Server 2013 Configure farms and databases Create and extend web applications Set up and scale service applications Deploy and manage sites/collections Implement BI solutions Integrate Excel Services and PowerPivot Configure enterprise content types and metadata Deploy Enterprise Search Manage documents and web content Brand your site Deliver social tools, including microblogging Back up and restore.